20′ five-point function from AdS5 × S 5 supergravity - Gonçalves, Vasco [UNESP]; Pereira, Raul; Zhou, Xinan (Springer Nature, 2019)
We develop new techniques to compute five-point correlation functions from IIB supergravity on AdS5 × S5. Our methods rely entirely on symmetry and general con- sistency conditions, and eschew detailed knowledge of the supergravity effective action. We demonstrate our methods by computing the five-point function of the 20′ operator, which is the superconformal primary of the stress tensor multiplet. We also develop systematic methods to compute the five-point conformal blocks in series expansions. Using the ex- plicit expressions of the conformal blocks, we perform a Euclidean OPE analysis of the 20′ five-point function. We find expected agreement with non-renormalized quantities and also extract new CFT data at strong coupling.
Keywords: AdS-CFT Correspondence; Conformal Field Theory; Scattering Amplitudes